An electrochemical sensing platform to determine tetrahydrozoline HCl in pure form, pharmaceutical formulation, and rabbit aqueous humor. Issue 22 (27th May 2020) - Mahmoud, Amr M.; Saad, Martin N.; Elzanfaly, Eman S.; Amer, Sawsan M.; Essam, Hebatallah M.
Abstract : In pharmaceutical industry and clinical applications, finding real-time analyzers with minimal sample preparation is a good aim. The presented solid-contact sensor offers a reasonable tool for selective, sensitive and eco-friendly analysis. Abstract : In the pharmaceutical industry, finding cost-effective and real-time analyzers that provide valid data is a good aim. The purpose of this work was to propose a link between the pharmaceutical industry and the recent innovations in solid-contact ion-selective electrodes (SC-ISEs) for the utilization of these electrodes as real-time analyzers to evaluate the concentration of tetrahydrozoline HCl in different matrices. The backbone of these new potentiometric sensors is the conjunction of calix[6]arene and (2-hydroxypropyl)-β-cyclodextrin as molecular recognition elements and a network of multi-walled carbon nanotubes as a solid transducer material between an ionophore-doped PVC membrane and microfabricated Cu electrodes. The proposed sensors were optimized to determine tetrahydrozoline, and their performances were assessed according to the IUPAC recommendations. The proposed solid-contact sensors were compared with liquid contact sensors, and the former sensors were found to be better than the latter sensors in terms of durability, handling, and easier adaptation to industry with comparable sensitivity. The measurements were implemented using phosphate buffer (pH: 6). The best obtained linearity range was 1 × 10 −2 to 1 × 10 −7 M, and the best LOD was 1 × 10 −8 M. The sensors with the best performance were successfully applied to determine tetrahydrozoline in a pharmaceutical eye preparation and rabbit tears. The obtained results were statistically compared to those obtained by the official method of analysis, and no significant difference was obtained. The eco-score of the method was assessed using the eco-scale tool and also compared with that of the official method. The proposed approach was validated according to the International Council for Harmonisation (ICH) guidelines.